Potential influence of landscape transition on stream water chemistry trends during the last decades in a karst catchment (Pyrenees, SW France) in a context of global environmental changes. (July 2022) - Ulloa-Cedamanos, F.; Probst, J.L.; Marais-Sicre, C.; Vrech, E.; Maire, E.; Probst, A.
Graphical abstract: Highlights: A method was developed to determine the landscape transition in a mountainous basin. An indicator of land cover change was proposed and applied to a set of images. Over the last 80 years, a progressive non-linear forest recolonization was evidenced. Rising trends in streamwater ions by 1979 were correlated with a 31% forest extension. Global warming and environment parameters have delayed and indirect effects on water quality. Abstract: Over the last century, lands used for livestock and agriculture have been progressively abandoned on mountains across Europe. The afforestation of abandoned agricultural lands leads to significant environmental impacts particularly in karst catchments, which are highly responsive to climate change and human disturbances. Due to the lack of long-term historical records and appropriate methods, these impacts are not yet well investigated. The remote Baget forested catchment (Pyrenees Mountains), where a long-term hydrochemical survey has been conducted since 1979, was chosen to develop a method for reconstructing the evolution of landscapes based on heterogeneous and multi-temporal satellite imagery and aerial photographs from 1942 onwards. An indicator of landscape change is proposed, based on three vegetation groups, compatible with the various supporting data . The spatio-temporal landscape evolution evidenced a regular increase of 31% in forest extension between 1942 and 2019, while pioneer (grassland and heathlands) and open forest (early woodland) stages showed an overall but uneven decrease, marked by an accelerated decline of the latter due to an increase in livestock activities. The trends of streamwater discharge and chemistry were related to these environmental changes. A set of processes influencing the changes in the hydrochemical patterns, particularly the increase in dissolved elements in streamwater originating from carbonate dissolution, is proposed and discussed. The forest recolonization (+0.05 Km 2 .yr −1 ) enhanced soil organic matter content, generating an increased pCO2 in soils, which in turn enhanced the carbonate dissolution, expressed by a concentration increase of + 5 μeq.L -1 .yr −1 for (Ca 2+ +Mg 2+ ) and of + 10 μeq.L -1 .yr −1 for HCO3 – . The steeper slope of HCO3 – could result from decreasing terrestrial Ca 2+ +Mg 2+ export together with decreasing SO4 2- leaching (−4 μeq.L -1 .yr −1 ) due to decreasing acid atmospheric deposition. In the meantime, the observed increase in air temperature (+0.03 °C.yr −1 ) favoured tree growth, litter decomposition and water demand by trees. This study has demonstrated the powerful indicator of linking the historical evolution of the landscape, quantified using images, to the observed trends in the hydrochemical composition of stream waters, to highlight the internal processes of the critical zone. However, because of nested effects, it still remains a challenge to strictly quantify their respective impact on streamwater chemistry.